Is There Migration-Related Inequity in Access to or in the Utilisation of Health Care in Germany? - Monika Sander (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper analyses immigrants' access to health care and utilisation of health care services in Germany. Thereby, it is investigated if there is inequity in access to or in the utilisation of health care services due to a lack of language skills or due to a lack of information about the health care system (approximated by years since migration)among first- and secondgeneration immigrants. The data used are drawn from eleven waves of the SOEP (1995-2006). With regard to the probability to contacta physician (as a proxy for access), German language skills are found to have no significant influence for all groups of immigrants. The hypothesis of inequity in access to health care due to access barriers caused by a lack of German language skills is therefore not supported by the data. However, mother tongue language skillsseem to be important for the contact probability of the first- and secondgeneration: Having only good or poor mother tongue language skills reduces the probability of a doctor contact. The effect is found to be significant for first- and second-generation men. For the frequency of doctor visits (utilisation), poor German language skills are found to exert a significant influence: Those reporting poor language skills have a lower expected number of doctor visits. The effect is found to be significant for first-generation men and for secondgeneration men and women. Hence, there seems to be inequity in health care utilisation due to a lack of German language skills. With the exception of first-generation men - where it is found that poor mother tongue language skills reduce the expected number of doctor visits significantly, no significant effect is found for mother tongue language skills. With regard to the duration of residence, the results indicate that years since migration have an impact on the contact decision of first-generation immigrant women, whereby a significant positive influence is found. Hence, missing knowledge about the health care system could create additional access barriers and yield inequity in access to health care in the group of firstgeneration women. The duration of residence seems to have no influence on the frequency decision.
Keywords: C23; D63; I10; 330; Utilisation of health care; inequity; immigrants; SOEP